Entre fios, nós e educações ambientais: narrativas ecologistas de mulheres de Cariacica/ES - Ribeiro, Márcia Cristina Mazocco (2021)
This research approaches movements related to the establishment of municipal policies for environmental education in the municipality of Cariacica, and the environmental educations that emerge in the ecology narratives of a group of women. The aim is to map the establishment processes of environmental education policies in the municipality of Cariacica, as well as to problematize the pedagogical and political contributions of pedagogical practices for environmental education that cross the school routine, which emerge along with ecology narratives of teachers and environmental educators and with the escrevivências – writing experiences – of a group of women from different administrative regions of the municipality. The intention is to map other environmental educations, ecologies and stories that were erased and silenced, but they resist. The subjects from this research and story are women here acknowledged as ecologists (REIGOTA, 1999). This research is close to the theoretical perspectives of Freire’s pedagogy, researches on environmental education by Marcos Reigota and Rodrigo Barchi, conceptions of ecology narratives by Soler Gonzalez and Andreia Ramos, and conversation networks by Nilda Alves. Furthermore, it searches for inspiration in the literature of Conceição Evaristo. For the production of data, we opted for conversational interviews, photographs, postcards, field diary and bibliographic research. The proposal of the educational product will be a set of materials that include 03 Podcast episodes, available in the digital accounts of Narradores da Maré, with a link to access the material, and 16 watercolor postcards, hand-painted, with the images of territories of affection and the escrevivências of women, in a narrative policy, in which subjects of the research and the story can narrate their memories, ecologies and environmental educations. Thus, we believe in the formative and pedagogical potential of those other ecologies and narratives towards a political environmental education, that enhance the participation of the community in the discussion of their local issues and in the policies of environmental education in the municipality of Cariacica.